2016
DOI: 10.1161/hypertensionaha.115.07065
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Blood Pressure in Girls With Turner Syndrome

Abstract: Cardiovascular disease is the major factor that reduces lifespan in Turner syndrome. High blood pressure (BP) is common in Turner syndrome and is the most easily treatable cardiovascular risk factor. We studied the prevalence of elevated screening systemic BP, awareness of the problem, and its clinical associations in a large group of girls attending the annual meeting of the Turner Syndrome Society of the United States. Among 168 girls aged 2 to 17 years, 42% had elevated screening BP (systolic and diastolic)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
2
16
1
Order By: Relevance
“…A more prominent clustering of metabolic comorbidities in 45,X monosomy were found. Our findings confirm previous observations that an abnormal metabolic profile appears at a relatively young age in girls with TS ( 8 , 11 , 12 , 24 27 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A more prominent clustering of metabolic comorbidities in 45,X monosomy were found. Our findings confirm previous observations that an abnormal metabolic profile appears at a relatively young age in girls with TS ( 8 , 11 , 12 , 24 27 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, in a substantial number of the girls in our study already displaying cardiometabolic risk factors during childhood the BMI percentile was normal. As in other studies, our findings showed that hypertension, impaired glucose metabolism and dyslipidemia were not associated with body weight in young girls with TS ( 7 , 24 27 ). It would therefore appear that these early metabolic derangements may be attributed to risk factors inherent to TS: impaired glucose metabolism—to pancreatic beta cell dysfunction and decreased insulin secretory response to glucose ( 8 , 12 ); abnormal circadian BP rhythm and elevated BP—to autonomic dysfunction with altered vascular tone ( 7 , 32 ).…”
Section: Discussionsupporting
confidence: 87%
“…Because hypertension is common in TS, maintenance of normal blood pressure may lessen risk of aortic events (281, 282,283). Since AoD appears to occur at smaller absolute and ASI in TS, it is reasonable to begin prophylactic medical therapies earlier than what has been recommended for other patient groups.…”
Section: Medical Managementmentioning
confidence: 99%
“…Although individuals with TS are frequently found to have systemic hypertension, and even though hypertension is a known risk factor for progressive cardiac dysfunction and aortopathy, little has been documented about definitions and management of systemic hypertension, specifically for women with TS (281). Individuals with TS have been considered to have systemic hypertension in several studies with frequency as high as 20-40% in childhood (282) and in as many as 60% of adults (191,314,315,316). Systemic hypertension may appear at early ages and continue through adulthood.…”
Section: Hypertensionmentioning
confidence: 99%
“…Although the cause of hypertension in Turner syndrome is still not clear, structural etiology as well as heart autonomic innervations, increased plasma renin activity (PRA), and parasympathetic neuropathy, can cause hypertension in Turner syndrome patients. Thus, hypertension is the most important modifiable risk factor for aortic dissection and rupture that occurs in young women with Turner syndrome [ 3 , 8 10 ]. Therefore, adults with Turner syndrome should undergo regular cardiac examinations and imaging studies to detect aortic root dilatation, cardiac valve disease, or other cardiovascular anomalies, as well as routine blood pressure (BP) monitoring [ 4 ].…”
Section: Introductionmentioning
confidence: 99%